Synthesis and characterization of AlPO4-5RT molecular sieve at room temperature - Venkatathri, N. (Journal of the Indian Chemical Society, 2006)
Aluminophosphate molecular sieve AlPO4-5RT (AlPO4-5, prepared at room temperature) have been synthesized using hexamethyleneimine template at room temperature for the first time. Gel composition Al2O3 : P2O5 : 1.16HEM : 45H(2)O aging for 12 h at room temperature, and in 24 h, 473 K are the standard reaction conditions for synthesis of AlPO4-5. Studies on above gel composition at room temperature shows the presence of AlPO4-5 crystals. Both the aluminophosphates have been characterized by elemental analysis, XRD, SEM, FT-IR, TG/DTA, and C-13, Al-27 and P-31 MASNMR techniques. XRD analysis of AlPO4-5RT shows that the presence of low intensed pseudobochmite sample. SEM shows the morphology nanosized crystals along with platelets. TG/DTA analysis reveals the presence of maximum five stages elimination of templates. Carbon and nitrogen analysis shows that the presence of four template molecules per unitcell. C-13 MASNMR analysis shows the interaction of template with structure of the framework. Al-27 MASNMR shows the presence of small amount of octahedral co-ordination besides the rest are in tetrahedral co-ordination. P-31 MASNMR shows the presence of two environmentally different tetrahedrally co-ordinated phosphorous atoms.
Keywords: Aluminophosphate; Molecular sieve

Incorporation of zirconium in medium-pore aluminophosphate molecular sieves with AEL framework - Ganguli, J. N.; Chakrabortty, Dhruba; Satyanarayana, C. V. V. (Microporous and Mesoporous Materials, 2008)
Zirconium incorporated alurninophosphate molecular sieves ZrAPO-11 was synthesized by hydrothermal method. The samples were characterized by X-ray diffraction (XRD), scanning electron microscopy, thermogravimetric/differential thermal analysis (TGA/DTA), diffuse reflectance UV-visible spectroscopy, magic-angle spinning nuclear magnetic resonance (MAS NMR) spectroscopy (P-31 and Al-27). The acidity of the materials were determined by temperature programmed desorption (TPD) of ammonia. X-ray diffraction and scanning electron microscopy reveals formation of crystalline material in pure phase. Thermal analysis shows higher template content in zirconium containing samples than the corresponding AlPOs. MAS NMR suggests incorporation of zirconium in the framework. TPD reveals that the ZrAPO-11 samples were of higher acidity than AIPO(4)-11 (c) 2007 Elsevier Inc. All rights reserved.
Keywords: AlPO4-11; Aluminophosphate; catalysis; Molecular sieve; ZrAPO-11

Incorporation of zirconium in medium-pore aluminophosphate molecular sieves with AFO framework - Chakrabortty, Dhruba; Ganguli, J. N.; Satyanarayana, C. V. V. (Microporous and Mesoporous Materials, 2011)
Zirconium substituted medium pore microporous aluminophosphate molecular sieve ZrAPO-41 was prepared by hydrothermal synthesis under autogenous pressure The formation of the pure phase was confirmed by powder X-ray diffraction (XRD) and scanning electron microscopy (SEM)The thermal behaviour of the material was investigated by carrying out thermogravimetric/differential thermal analysis (TGA/DTA) The zirconium environment was studied by magic-angle spinning nuclear magnetic resonance (MAS NMR) spectroscopy which suggests incorporation of zirconium into the framework UV-Visible diffuse reflectance study also supports the claim The temperature programmed desorption (TPD) of ammonia reveals that the acidity of ZrAPO 41 samples is higher than that of pure AlPO4-41 The catalytic activity of the samples was investigated through phenol hydroxylation reaction The result show hi E her catalytic activity for ZrAPO-41 samples compared to AlPO4-41 (C) 2010 Elsevier Inc All rights reserved
Keywords: AFO; Aluminophosphate; catalysis; Molecular sieve; ZrAPO 41